Effects Of Self Service Attributes On Consumer Decision In Choosing A Supermarket - Hadiwidjaja, Meilany (2009)
This study examines the factors that influence customer's decision-making in choosing Alfa supermarket. This study intends to identify the role of dimensional attributes of supermarket that influence consumer decision in choosing Alfa supermarket, and to know which one is more dominant / important among the dimensional attributes of the supermarket.